Criterion validity of the Saltin-Grimby Physical Activity Level Scale in adolescents. The Fit Futures Study. - Sigurd K Beldo; Nils Abel Aars; Tore Christoffersen; Anne-Sofie Furberg; Peder A Halvorsen; Bjørge Herman Hansen; Alexander Horsch; Edvard H Sagelv; Shaheen Syed; Bente Morseth (PLoS ONE, 2022)
Background The Saltin-Grimby Physical Activity Level Scale (SGPALS) is commonly used to measure physical activity (PA) in population studies, but its validity in adolescents is unknown. This study aimed to assess the criterion validity of the SGPALS against accelerometry in a large sample of adolescents. A secondary aim was to examine the validity across strata of sex, body mass index (BMI), parental educational level, study program and self-reported health. Methods The study is based on data from 572 adolescents aged 15-17 years who participated in the Fit Futures Study 2010-11 in Northern Norway. The participants were invited to wear an accelerometer (GT3X) attached to their hip for seven consecutive days. We used Spearman's rho and linear regression models to assess the validity of the SGPALS against the following accelerometry estimates of PA; mean counts/minute (CPM), steps/day, and minutes/day of moderate-to-vigorous physical activity (MVPA). Results The SGPALS correlated with mean CPM (ρ = 0.40, p<0.01), steps/day (ρ = 0.35, p<0.01) and MVPA min/day (ρ = 0.35, p<0.01). We observed no differences between correlations within demographic strata (all p>0.001). Higher scores on SGPALS were associated with a higher CPM, higher number of steps per day and more minutes of MVPA per day, with the following mean differences in PA measurements between the SGPALS ranks: CPM increased by 53 counts (95% CI: 44 to 62), steps/day increased by 925 steps (95% CI: 731 to 1118), and MVPA by 8.4 min/day (95% CI: 6.7 to 10.0). Mean difference between the highest and lowest SGPALS category was 2947 steps/day (6509 vs. 9456 steps/day) and 26.4 min/day MVPA (35.2 minutes vs 61.6 minutes). Conclusion We found satisfactory ranking validity of SGPALS measured against accelerometry in adolescents, which was fairly stable across strata of sex, BMI, and education. However, the validity of SGPALS in providing information on absolute physical activity levels seem limited.